Air Force reference atmospheres - Cole, Allen E.; Kantor, Arthur J., author.; U.S. Air Force Geophysics Laboratory.
Sets of mean monthly reference atmospheres that describe seasonal changes in the vertical distributions of temperature, density, and pressure up to 90 km are presented for 15 intervals of latitude between the equator and pole. Specialized atmospheres are included that portray longitudinal variations in monthly median values of temperature, density, and pressure during winter months. Other models illustrate the magnitude of the changes in the vertical distributions of these atmospheric properties during winter warmings and coolings of the stratosphere and mesosphere in arctic and subarctic regions. Estimates of the day-to-day variations around the monthly median values of temperature and density are provided for each set of models. (Author). Research supported by the Air Force Geophysics Laboratory, Air Force Systems Command, United States Air Force, Hanscom AFB, Massachusetts. Chiefly tables. Meteorology Division Project 6670. ADA058505 (from http://www.dtic.mil). "28 February 1978." Includes bibliographical references (pages 37-39). Sets of mean monthly reference atmospheres that describe seasonal changes in the vertical distributions of temperature, density, and pressure up to 90 km are presented for 15 intervals of latitude between the equator and pole. Specialized atmospheres are included that portray longitudinal variations in monthly median values of temperature, density, and pressure during winter months. Other models illustrate the magnitude of the changes in the vertical distributions of these atmospheric properties during winter warmings and coolings of the stratosphere and mesosphere in arctic and subarctic regions. Estimates of the day-to-day variations around the monthly median values of temperature and density are provided for each set of models. (Author). Mode of access: Internet.